Trends and Patterns in the Public Awareness of Palliative Care, Euthanasia, and End-of-Life Decisions in 3 Central European Countries Using Big Data Analysis From Google: Retrospective Analysis - Matthias Huemer; Daniela Jahn-Kuch; Guenter Hofmann; Elisabeth Andritsch; Clemens Farkas; Walter Schaupp; Eva Katharina Masel; Philipp J Jost; Martin Pichler (JMIR Publications, 2021)
BackgroundEnd-of-life decisions, specifically the provision of euthanasia and assisted suicide services, challenge traditional medical and ethical principles. Austria and Germany have decided to liberalize their laws restricting assisted suicide, thus reigniting the debate about a meaningful framework in which the practice should be embedded. Evidence of the relevance of assisted suicide and euthanasia for the general population in Germany and Austria is limited. ObjectiveThe aim of this study is to examine whether the public awareness documented by search activities in the most frequently used search engine, Google, on the topics of palliative care, euthanasia, and advance health care directives changed with the implementation of palliative care services and new governmental regulations concerning end-of-life decisions. MethodsWe searched for policies, laws, and regulations promulgated or amended in Austria, Germany, and Switzerland between 2004 and 2020 and extracted data on the search volume for each search term topic from Google Trends as a surrogate of public awareness and interest. Annual averages were analyzed using the Joinpoint Regression Program. ResultsImportant policy changes yielded significant changes in search trends for the investigated topics. The enactment of laws regulating advance health care directives coincided with a significant drop in the volume of searches for the topic of euthanasia in all 3 countries (Austria: −24.48%, P=.02; Germany: −14.95%, P<.001; Switzerland: −11.75%, P=.049). Interest in palliative care increased with the availability of care services and the implementation of laws and policies to promote palliative care (Austria: 22.69%, P=.01; Germany: 14.39, P<.001; Switzerland: 17.59%, P<.001). The search trends for advance health care directives showed mixed results. While interest remained steady in Austria within the study period, it increased by 3.66% (P<.001) in Switzerland and decreased by 2.85% (P<.001) in Germany. ConclusionsOur results demonstrate that legal measures securing patients' autonomy at the end of life may lower the search activities for topics related to euthanasia and assisted suicide. Palliative care may be a meaningful way to raise awareness of the different options for end-of-life care and to guide patients in their decision-making process regarding the same.